TELAAH KONSEP TAFWĪḌ DAN TAKWIL PADA AYAT-AYAT MUTASHĀBIHĀT DALAM AL-QUR’AN DAN TERJEMAHANNYA TERBITAN KEMENAG RI EDISI PENYEMPURNAAN TAHUN 2019 - Maimoen, Abdul Ghofur; Amiroh, Faiqotul (AL ITQAN: Jurnal Studi Al-Qur'an, 2021)
This study reveals the concepts of tafwīḍ and takwil in the mutashābihāt verses in the Qur'an and its translation published by the Indonesian Ministry of Religion in the 2019 edition of the perfected edition. Both concepts also have an effect on the translation of the Qur'an initiated by the Ministry of Religion of the Republic of Indonesia. This research uses the descriptive-analytic method through literature study using mutashābihāt, tafwīḍ, and takwil theories. Based on the analysis that has been done, this study concludes that the concept of tafwīḍ is translated by the Ministry of Religion of the Republic of Indonesia with two models, namely (1) translating according to its basic meaning without being accompanied by footnotes, and (2) translating according to its basic meaning, accompanied by explanations in footnotes. While the takwil concept is translated into three models, namely (1) turning it away from the meaning of āhir without adding an explanation, (2) allowing the meaning of āhir to be accompanied by an explanation in brackets, and (3) allowing the meaning of āhir to be accompanied by an explanation in the footnote.